Experience of African American Surrogate Decision Makers of Patients With Dementia. Issue 1 (2nd December 2021) - Hart, Alysha S.; Matthews, Alicia K.; Arslanian-Engoren, Cynthia; Patil, Crystal L.; Krassa, Teresa J.; Bonner, Gloria J.
Abstract : Dementia cases are expected to grow for African Americans and surrogate decision makers (SDMs) will have a significant role at the end of life (EOL). This qualitative exploratory case study used Cognitive Task Analysis and an integrated conceptual framework to understand the EOL decision experience of African American SDMs for patients with advanced dementia. Using a holistic multiple-case design, 8 African American SDMs were interviewed about their experiences with the decision-making process, including role acceptance, role enactment, and emotional outcomes of decision making. Thirteen themes germane to understanding the EOL decision experience of African American SDMs were identified. Findings suggest African American SDMs often lack sufficient knowledge of disease prognosis and intervention options to make informed treatment choices at EOL. In particular, African Americans extend the caregiver role to SDM for patients with dementia at EOL without being fully aware of the role and decision-making responsibilities. Surrogates lacked a general understanding of EOL options resulting in underutilization of hospice and palliative care and subsequent regret, and few interventions exist to improve the uptake of EOL care services. There is a need to develop culturally appropriate role preparation, education, and decision support to improve EOL treatment decisions and emotional adjustment of surrogates of patients with advanced dementia, which should be rendered early and throughout the illness trajectory.